Log odds of positive lymph nodes is superior to the number- and ratio-based lymph node classification systems for colorectal cancer patients undergoing curative (R0) resection - Fang, Hong Yan; Yang, Hui; He, Zhong Shi; Zhao, Hong; Fu, Zhen Ming; Zhou, Fu Xiang; Zhou, Yun Feng (Molecular and clinical oncology, 2017)
The metastatic lymph node status (N classification) is an important prognostic factor for patients with colorectal cancer (CRC). The aim of the present study was to evaluate and compare the prognostic assessment of three different lymph node staging methods, namely standard lymph node (pN) staging, metastatic lymph node ratio (LNR) and log odds of positive lymph nodes (LODDS) in CRC patients who undergo curative resection (R0). Data were retrospectively collected from 192 patients who had undergone R0 resection. Kaplan-Meier survival curves, Cox proportional hazards model and accuracy of the three methods (pN, LNR and LODDS) were compared to evaluate the prognostic effect. Univariate analysis demonstrated that pN, LNR and LODDS were all significantly correlated with survival (P=0.001, P<0.001 and P<0.001, respectively). The final result of the 3-step multivariate analysis demonstrated that LODDS was superior to the other two N categories. Patients in the same pN or LNR classifications may be classified into different LODDS stages with different prognoses. Thus, LODDS may be a meaningful prognostic indicator and superior to the pN and LNR classifications in CRC patients who undergo curative (R0) resection.